(untitled) - Quốc Chấn (Hà Nội, 2015)
Giới thiệu tiểu sử và chiến công của các tướng lĩnh thời Trần như: Lê Tần, Hưng Đạo Vương Trần Quốc Tuấn, Trần Quang Khải, Trần Khánh Dư, Trần Nhật Duật...
Keywords: Tác gia Việt Nam,Authors, Vietnamese